2018
DOI: 10.1097/olq.0000000000000695
|View full text |Cite
|
Sign up to set email alerts
|

Sexually Transmitted Infection Testing of HIV-Positive Medicare and Medicaid Enrollees Falls Short of Guidelines

Abstract: Sexually transmitted disease rates are rising rapidly among men who have sex with men, yet sexually transmitted disease screening for people living with HIV is well below the Centers for Disease Control and Prevention recommendations, especially for chlamydia and gonorrhea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Several studies have suggested that MSM are not screening for bacterial STIs as frequently as recommended. This has been quantified by HIV status, 19 health insurance status, 20 race/ethnicity, 21 and participation in HIV prevention programs. 22 However, most of these studies quantify gaps in testing using period prevalence measures rather than rate-based measures.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that MSM are not screening for bacterial STIs as frequently as recommended. This has been quantified by HIV status, 19 health insurance status, 20 race/ethnicity, 21 and participation in HIV prevention programs. 22 However, most of these studies quantify gaps in testing using period prevalence measures rather than rate-based measures.…”
Section: Discussionmentioning
confidence: 99%
“…Provider adherence to screening recommendations (Table 1) put out by the CDC, the US Preventive Services Task Force (USPSTF), and the American College of Obstetricians and Gynecologists (ACOG) is crucial to the success of syphilis intervention strategies. Several studies suggest less than adequate provider adherence to STI screening practices; this includes low syphilis testing rates among positive HIV individuals, 50,51 missed opportunities for preventing congenital syphilis cases, 52 and low syphilis testing for females who gave birth to stillborns. 53 Health care systems should look to implement quality control initiatives that monitor provider adherence to syphilis screening, and third party payers should consider implementing reimbursement incentives that reward health systems for better screening practices.…”
Section: Medical Provider's Rolementioning
confidence: 99%
“…Whereas data are lacking in Germany, studies from UK, USA, and Canada suggest that STI testing uptake in HIV cohorts remains suboptimal, especially in MSM [15][16][17][18]. In a multicenter study in several HIV cohorts in USA, annual testing rate for NG/CT was only 39% of patients engaged in care compared to 77% testing rate for syphilis, although most patients reported sexual behavior with a higher possibility for STI transmission [17].…”
Section: Introductionmentioning
confidence: 99%